Vida de la madre Catalina de Cardona por fray Juan de la Miseria. Un texto hagiográfico desconocido del siglo XVI (Bancroft Library, UCB, Fernán Núñez Collection, vol. 143) - Cortijo Ocaña, Adelaida (Dicenda. Estudios de lengua y literatura españolas, 2003)
La vida de la madre Catalina de Cardona has been preserved in a manuscript held at The Bancroft Library, University of California (Berkeley). This manuscript includes a previouslyunknown narrative of the life and deeds of a curious 16th century female religious reformer (Catalina de Cardona). In addition to the manuscript’s importance in that it provides us with many previously-unknown details on the life of Catalina de Cardona, it is paramount in that it was written by St. Teresa de Jesús’s great painter, the Italian born fray Juan de la Miseria.